3D reconstruction of a gallbladder duplication to guide LC: A case report and literature review. Issue 8 (22nd February 2023) - Ye, Yong Qing; Liang, Qing; Li, En Ze; Gong, Jing Lin; Fan, Jing Ming; Wang, Ping
Abstract : Rationale: Gallbladder duplication is a congenital aberration of the biliary tree, which is rarely encountered in the abdomen. It is a challenge that can be encountered by surgeons and is associated with an increased risk of complications after cholecystectomy. More than 50% of gallbladder duplication cases were undetected on preoperative traditional imaging. In this study, a case of gallbladder duplication in a patient with mild abdominal pain detected using preoperative 3-dimensional (3D) reconstruction of the gallbladder was described for the first time. Patient concerns and diagnosis: We present a case of gallbladder duplication in a 32-year-old man who was referred to our hospital for recurrent right upper quadrant abdominal pain without any other significant history. Interventions and outcomes: He underwent a 3D reconstruction technique as a supplement for gallbladder duplication that could not be diagnosed using magnetic resonance cholangiopancreatography or other traditional tools. Compared with other diagnostic tools, 3D reconstruction is more visual and accurate for diagnosing gallbladder duplication and guiding laparoscopic cholecystectomy without ductal injuries or other complications. Conclusion: Gallbladder duplication is an extremely rare biliary anatomical anomaly; failure to recognize it perioperatively exposes the patient to an increased risk of bile duct injuries. We review 28 cases of missed gallbladder duplication and conclude that less 50% of gallbladder duplication cases were detected via preoperative traditional imaging. We present a case and find that the 3D reconstruction technique can be used as a supplement for gallbladder duplication that could not be diagnosed by using magnetic resonance cholangiopancreatography or other tools. The value of using 3D reconstruction of gallbladder duplication is feasible and innovative, and facilitates guiding to laparoscopic cholecystectomy.